Empowered Voices of Serenity: The Feminist Legacy and The Contribution of Buddhist Bhikkunis in Ancient India - Das, Raka; Singh, Pushpraj; Khan, Ahkilesh Kumar (Journal of Cultural Analysis and Social Change, 2025)
This paper explores the significant yet often underrecognized contributions of Buddhist Bhikkunis in ancient India, through a feminist lens. By delving into historical texts, feminist analyses, and contemporary studies, it sheds light on the multifaceted roles Bhikkunis played in shaping early Buddhist practices and advancing the status of women in ancient Indian society. Despite facing patriarchal constraints within and outside the Sangha, Bhikkunis were pivotal in challenging societal norms, fostering educational and religious communities, and contributing to the spiritual and social fabric of their time. The study reveals how Bhikkunis navigated the complexities of their religious and social milieu to make enduring contributions to Buddhism and feminist thought. Their narratives, teachings, and resilience offer profound insights into the dynamics of gender, religion, and power in ancient India, highlighting their role not just as religious figures but as early feminists who laid down a legacy of spiritual equality and social change. This paper not only honours their contributions but also contributes to the ongoing discourse on gender equality within religious practices, underscoring the need for a nuanced understanding of feminism's historical roots in South Asian religious traditions.